Curcumin Analogs PGV-1 and CCA-1.1 Induce Cell Cycle Arrest in Human Hepatocellular Carcinoma Cells with Overexpressed MYCN - Moordiani Moordiani; Dhania Novitasari; Ratna Asmah Susidarti; Muthi' Ikawati; Jun-ya Kato; Edy Meiyanto (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Liver cancer is the third leading mortality in cancer. Curcumin shows effective anticancer potency against various cancer including liver cancer. The synthesized curcumin analog compounds Pentagamavunone-1 (PGV-1) and Chemoprevention Curcumin Analog-1.1 (CCA-1.1) have been well studied in breast, leukemia, and colon cancer cells with better potency than curcumin itself, yet their cytotoxic activities were not known in liver cancer cells. Thus, this study was conducted to elevate the anticancer effect of these curcumin analogs against hepatocellular carcinoma (HCC) cells in vitro, specifically in MYCN-expressing cells, based on its cellular physiology.METHODS: JHH-7 cells were used as the HCC cell model with high expression of MYCN. The viability of the cells was observed using trypan blue exclusion method while cell cycle profile and intracellular reactive oxygen species (ROS) levels were quantified by means of flow cytometry. Chromosomal staining with Hoechst was applied to determine the cell cycle arrest phase, whilst X-gal staining was used to assess the cellular senescence activity.RESULTS: The result of current study presented that the growth inhibitory activity of PGV-1 as well as CCA-1.1 in JHH-7 cells was associated with the cell cycle arrest and cellular senescence. Both curcumin analogs PGV-1 and CCA-1.1 ultimately induced mitotic arrest (p<0.001) better than curcumin. Moreover, PGV-1 and CCA-1.1 similarly increased the senescent cells that partly mediated through ROS elevation. The transcription level of MYCN was not altered upon treatment with curcumin and its analogs in JHH-7 cells, suggesting that molecular mechanism of the inhibitory effect was independent from MYCN signaling.CONCLUSION: Taken together, these observations revealed that both PGV-1 and CCA-1.1 potentially serve as multi-targeted curcumin-based compounds and lead to promising anti-hepatocellular cancer agents.KEYWORDS: Curcumin analogs, hepatocellular carcinoma, mitotic arrest, MYCN